Quantification of [11C]FLB 457 Binding to Extrastriatal Dopamine Receptors in the Human Brain - Olsson, Hans; Halldin, Christer; Swahn, Carl-Gunnar; Farde, Lars (Journal of cerebral blood flow and metabolism, 1999)
Positron emission tomography (PET) has hitherto been used to examine D2 dopamine receptor binding in the striatum, a region with a high density of receptors. Research has been hampered by the lack of suitable radioligands for detection of the low-density D2 dopamine receptor populations in the limbic and cortical dopamine systems that are implicated in the patophysiology of schizophrenia. [11C]FLB 457 is a new radioligand with the very high affinity of 20 pmol/L (Ki) for the D2 and D3 dopamine receptor subtypes. This study in eight healthy subjects was designed to evaluate the suitability of [11C]FLB 457 for quantification of extrastriatal D2/D3 dopamine receptors. PET-data were acquired in the three-dimensional mode and the arterial input function was corrected for labeled metabolites. The standard three-compartment model and four derived approaches were applied to calculate and compare the binding potentials. Besides the striatum, conspicuous radioactivity was found in extrastriatal regions such as the thalamus, the anterior cinguli, and the temporal and frontal cortices. The time activity curves could be described by the three compartment model. The different approaches gave similar binding potential values and the rank order between regions was consistent with that found in vitro. The short time of a PET measurement using [11C]FLB 457 (63 minutes) seemed not to be sufficient for reliable determination of the high binding potential in the striatum. These results are of principal importance because they show the potential for PET quantification of minute receptor populations in the human brain.